Experimental assessment of cumulative temperature and UV-B radiation effects on Mediterranean plankton metabolism - Garcia-Corral, Lara S.; Martinez-Ayala, Juan; Duarte, Carlos M.; Agusti, Susana (Frontiers in Marine Science, 2015)
The Mediterranean Sea is a vulnerable region for climate change, warming at higher rates compare to the global ocean. Warming leads to increased stratification of the water column and enhanced the oligotrophic nature of the Mediterranean Sea. The oligotrophic waters are already highly transparent, however, exposure of Mediterranean plankton to ultraviolet radiation (UV-B and UV-A) may increase further if the waters become more oligotrophic, thereby, allowing a deeper UV radiation penetration and likely enhancing impacts to biota. Here we experimentally elucidate the cumulative effects of warming and natural UV-B radiation on the net community production (NCP) of plankton communities. We conducted five experiments at monthly intervals, from June to October 2013, and evaluated the responses of NCP to ambient UV-B radiation and warming (+3ºC), alone and in combination, in a coastal area of the northwest Mediterranean Sea. UV-B radiation and warming lead to reduced net community production and resulted in a heterotrophic (NCP<0) metabolic balance. Both UV-B radiation and temperature, showed a significant individual effect in NCP across treatments and time. However, their joint effect showed to be synergistic as the interaction between them (UV x Temp) was statistically significant in most of the experiments performed. Our results showed that both drivers, would affect the gas exchange of CO2-O2 from and to the atmosphere and the role of plankton communities in the Mediterranean carbon cycle